WASIAT WAJIBAH TERHADAP ANAK ANGKAT (TINJAUAN FILSAFAT HUKUM ISLAM PASAL 209 KOMPILASI HUKUM ISLAM) - Nadya Faizal; Asni Zubair (Institut Agama Islam Negeri Bone, 2020)
AbstractThe legal status of the adopted child in The Compilation of Islamic Law are the status of marriage, the adopted child does not belong to the group who are forbidden to get marriage with adoptive parents, they are not in relationship with their adoptive parents, and they are not mahram from them. Furtheremore, inheritance status of the adopted child is that it does not fall within the category of a person entitled to inheritance. This means that between adopted child and his adoptive parents there is no relationship of inheriting with their adoptive parents, but in The Compilation of Islamic Law in article 209 opens the opportunity for him to receive a will or grant from his adoptive parents. The legal status of the provision of wills to the adopted child in article 209 of The Compilation of Islamic Law, the recipient of the wills is the child who should be raptured from among the close relatives, if no one then turns to the children of the poor, orphans, and children who are in weak economy class, or the child‟s findings (al-laqith).The holder of a will is a person who has a lot of property so as to allow not to reduce the acquisition of heritage treasures for the division of inheritance.